2010
DOI: 10.1016/j.jvs.2010.05.107
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the standard bolia technique versus subintimal recanalization plus Viabahn stent graft in the management of femoro-popliteal occlusions

Abstract: Combining subintimal angioplasty with a stent graft in femoro-popliteal lesions does not improve patency. The limb salvage rate remains high after addition of a stent graft. Rigorous monitoring is recommended to diagnose and treat restenosis early in order to improve patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…Boufi et al deployed a mean of 1.6 ± 0.65 (range, 1–3) stent grafts, with an average total length of 21.25 ± 10.26 cm . At one year, primary patency was 61.8%, which is lower than our outcomes, despite the fact that the patients we treated had longer lesion lengths (27.7 ± 13.4 cm in the AK group, 35.9 ± 16.6 cm in the BK group).…”
Section: Discussioncontrasting
confidence: 58%
“…Boufi et al deployed a mean of 1.6 ± 0.65 (range, 1–3) stent grafts, with an average total length of 21.25 ± 10.26 cm . At one year, primary patency was 61.8%, which is lower than our outcomes, despite the fact that the patients we treated had longer lesion lengths (27.7 ± 13.4 cm in the AK group, 35.9 ± 16.6 cm in the BK group).…”
Section: Discussioncontrasting
confidence: 58%
“…However, to date, either selective stenting or full-lesion stenting (i.e., ''fullmetal jacket'') has not proved its superiority compared with plain balloon angioplasty [13,21]. Of interest, in a recent study by Boufi et al, there was no primary patency benefit by employment of a covered stent to treat the whole subintimal tract [15]. In our series, stenting was deemed necessary in 70.5% of the cases, all of which resulted in excellent initial outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, predictors for better angiographic patency after SIA have not been adequately investigated so far. In addition, the role of bare stent or stent-graft placement during subintimal recanalization of chronic total occlusions (CTOs) has been only touched on [12][13][14][15]. The investigators herein report the results of a prospective single-center registry with the aim to investigate the immediate result as well as the longterm clinical and angiographic outcome of SIA plus bailout stenting for the treatment of chronic total occlusive atherosclerotic disease of lesions located in the SFA and/or PA.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Boufi et al 6 demonstrated that combining SA with a stent-graft along the entire subintimal tract did not improve patency when compared to not receiving a stent. [5][6][7][8][9][10]14 Furthermore, our outcomes were superior compared with the data from Antusevas et al 9 As we reported, we routinely implanted a stent at the proximal stump to keep the entry into the subintimal channel open, and we tried not to cover long lesions with multiple stents because we wanted to avoid stent fractures or difficulties during future bypass surgery. [7][8][9][10]14 In the present study, the 1 and 3 years rates for freedom from restenosis (77% and 59%, respectively) were comparable to previous studies.…”
Section: Discussionmentioning
confidence: 63%